Implementation Of The Karang Taruna Work Program In Mundakjaya Village, Cikedung District, Indramayu Regency - Didik Himmawan; Astri Racmawati (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2024)
This research article aims to descriptively analyze the strategies of Mundakjaya village teenagers in implementing the program to support orphans, how to implement and manage the compensation program for orphans, what are the supporting and inhibiting factors for implementing the compensation program for orphans. The method used is a qualitative method. Several primary and secondary references are taken from field research and leading journals. This data is collected through analysis documentation. The results of the research show that the implementation of Karang Taruna's work program in Mundakjaya Village in supporting orphans, namely the strategy of collaborating with a brand, selling the product and then donating the profits to support orphans is very beneficial for the living needs of the orphans as well as a form of education for the community. It's not only the youth but also all groups who are involved in supporting orphans in the Mundakjaya village of the Munjul complex.